Investigation of Wound Healing and Anti-Inflammatory Activities of Solvent Fractions of 80% Methanol Leaf Extract of Achyranthes aspera L. (Amaranthaceae) in Rats - Mengie T; Mequanente S; Nigussie D; Legesse B; Makonnen E (Dove Medical Press, 2021)
Teklie Mengie,1 Solomon Mequanente,2 Dereje Nigussie,3 Belete Legesse,4 Eyasu Makonnen2,4 1Department of Pharmacy, College of Health Science, Debre Tabor University, Debre Tabor, Ethiopia; 2Department of Pharmacology & Clinical Pharmacy, School of Pharmacy, College of Health Science, Addis Ababa University, Addis Ababa, Ethiopia; 3Vaccines and Diagnostic Research Directorate, Ethiopian Public Health Institute, Addis Ababa, Ethiopia; 4Center for Innovative Drug Development & Therapeutics Trial in Africa (CDT-Africa), College of Health Science, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Teklie MengieDepartment of Pharmacy, College of Health Science, Debre Tabor University, P.O. Box: 272, Debre Tabor, 6300, EthiopiaTel +251 910111531Email mikrmengie21@gmail.comIntroduction: The various fractions of leaves of Achyranthes aspera L. (A. aspera) have not yet been explored scientifically for in-vivo wound healing and anti-inflammatory activities. The objective of this study was, therefore, to evaluate in-vivo wound healing and anti-inflammatory activities of solvent fractions of 80% methanol leaf extract of A. aspera in rats.Methods: The 80% methanol leaf extract of A. aspera was fractionated with chloroform, n-butanol and water. Wound healing and anti-inflammatory activities were evaluated using excision and incision wound models, rat paw edema and cotton pellet-induced granuloma models, respectively. For wound healing activity, fractions were evaluated at 5 and 10% ointments. The positive control groups were treated with nitrofurazone 0.2% ointment. Simple ointment treated for excision wound model and untreated for incision wound model rats were assigned as negative controls. For anti-inflammatory activity, fractions were evaluated at 100, 200 and 400mg/kg. Positive control groups were treated with indomethacin 10mg/kg for both rat paw edema and cotton pellet-induced granuloma models. The 2% Tween 80 treated rats were assigned as negative controls for both anti-inflammatory activity models. All groups comprised of 6 rats and treatment administrations were made topically and orally for evaluation of wound healing and anti-inflammatory activities.Results: The 10% w/w chloroform fraction ointment revealed a high percentage of wound contraction and reduced period of epithelialization (p < 0.01). Chloroform fraction was also found to be the most active fraction, which demonstrated the maximum percentage inhibition of edema (52.50%; p < 0.01) and transudative and proliferative component of chronic inflammation (37.52 and 52.81%; p < 0.01), which was comparable to indomethacin.Conclusion: Data obtained from this study collectively indicated that a chloroform fraction of 80% methanol leaf extract of A. aspera possessed significant wound healing and anti-inflammatory activities.Keywords: Achyranthes aspera, wound healing, carrageenan-induced paw edema, cotton pellet granuloma